The Influence Of Celebrity Endorsers And Electronic Word Of Mouth On Purchasing Decisions For Scarlett Products For Female Students Of Gontor Darussalam University - Nadila, Nur Putri; Abidin, Mohammad Zaenal (Islamic Business and Management Journal, 2024)
This study aims to determine the effect of Celebrity Endorser and Electronic Word Of Mouth on Purchasing Decisions for Scarlett consumers, namely students of Darussam Gontor University. This research method is descriptive quantitative, using data analysis collected and tested using multiple linear regression analysis. The sample used was 314 respondents. The results showed that Celebrity Endorser had a positive and significant effect on purchasing decisions of 0.696. E-WOM has a positive and significant effect on purchasing decisions of 0.636. Through the coefficient of determination test, it is proven that Celebrity Endorser and E-WOM on Purchasing Decisions for Scarlett consumers at Darussalam Gontor University students are 52.2%, while the remaining 47.8& is explained by other variables outside this research model. In summary, the two variables, namely Celebrity Endorser and E-WOM, have a positive and significant effect on purchasing decisions for Scarlett female consumers at Darussalam Gontor University.